1991
DOI: 10.1002/1097-0142(19910515)67:10<2560::aid-cncr2820671028>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Expression of glutathione S-transferase-π messenger rna in human esophageal cancers

Abstract: The expression of human glutathione S-transferase-r (GST-r) in resected primary esophageal tumors and in matching normal esophageal mucosa from 25 patients undergoing radical surgery was measured by RNA blot hybridization. The RNA transcript levels of GST-r in the tumor tissues were higher than those in normal tissues in 20 of 25 cases (80%). The mean G S T -r mRNA value in the tumor tissues (n = 25) was significantly ( P < 0.01) elevated as compared with that in background mucosa (n = 29), and in ten of 25 tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…However, we have found that the level of GST-P1 in cancerous tissue was significantly lower than the level in normal oesophageal tissue (Figure 3). This was contrary to what others have found (Tsuchida et al, 1989;Ishioka et al, 1991) although they determined blood and not tissue levels. However, our results were not unexpected since a phenomenon was observed in cancer, where GST-P1 was extruded into the blood as the inactive monomer (Kura et al, 1996).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, we have found that the level of GST-P1 in cancerous tissue was significantly lower than the level in normal oesophageal tissue (Figure 3). This was contrary to what others have found (Tsuchida et al, 1989;Ishioka et al, 1991) although they determined blood and not tissue levels. However, our results were not unexpected since a phenomenon was observed in cancer, where GST-P1 was extruded into the blood as the inactive monomer (Kura et al, 1996).…”
Section: Resultsmentioning
confidence: 95%
“…What is the case then in oesophageal cancer? In 80% of the patients, the resected primary oesophageal cancer showed that the RNA transcript levels of GST-P1 were significantly elevated (Ishioka et al, 1991). However, in contrast, Sasano et al (1993) found that with both in situ hybridization and immunohisto chemistry assessments, GST-P1 was detected as strongly in normal oesophageal mucosa as in cancer.…”
mentioning
confidence: 99%
“…In addition, since GSTs are involved in modulation of expression of other drug metabolizing proteins, polymorphism in GST may influence other defense mechanisms, thereby indirectly conferring a differential risk for development of cancer. [19] GSTs, particularly its class-Pi are predominantly expressed in human epithelial cells in the normal squamous esophagus epithelium [16,[20][21][22] and it has been used as the marker of gastrointestinal (G.I) carcinoma. Earlier we reported that the level of class P GST is elevated in tissue biopsies obtained from SCC patients who underwent surgery or upper gastro-digestive endoscopic operation when compared to normal samples.…”
Section: Discussionmentioning
confidence: 99%
“…Among the isozymes, the pi class enzyme GSTP1-1 is the most widely distributed and has been well studied in cancer. Increased expression of GSTP1-1 has been reported in a number of cancer types, including colon (Mulder et al, 1995), stomach (Peters et al, 1990), oesophagal (Ishioka et al, 1991), head and neck (Wang et al, 1997). An association between increased GSTP1-1 expression and resistance to cytotoxic drugs has also been established with breast cancer cells (Batist et al, 1986).…”
Section: Introductionmentioning
confidence: 99%